Landscape Archaeology between Art and Science From a Multi- to an Interdisciplinary Approach - Kluiving, Sjoerd J.; Guttmann-Bond, Erika (Landscape and Heritage Research, 2012)
This volume contains thirty-five papers from a 2010 conference on landscape archaeology focusing on the definition of landscape as used by processual archaeologists, earth scientists, and most historical geographers, in contrast to the definition favored by postprocessual archaeologists, cultural geographers, and anthropologists. This tension provides a rich foundation for discussion, and the papers in this collection cover a variety of topics including: how do landscapes change; how to improve temporal, chronological, and transformational frameworks; how to link lowlands with mountainous areas; applications of scale; new directions in digital prospection and modeling techniques; and the future of landscape archaeology.